PENGARUH PROMOSI JABATAN, INSENTIF DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT ALCO DANA MANDIRI - Alafiah, Siti; Raymond, Raymond (LPPM Universitas Putera Batam, 2021)
Along with that developments this business worlds and also increasingly tough competition, a company must do something to survive and achieve the goals that have been previously set. Human resources (HR) are important at company cause humans resourcing will affect the desired output of the company, qualified employees are an advantage for a company, This study aims to determine the effect of job promotion, incentives and work motivation on the performance of PT Alco Dana Mandiri employees. That studies uses quantitative research methods where questionnaires are distributed as instruments in collecting data. This type of research is quantitative research. The population of this research is all employees who work at PT Alco Dana Mandiri, amounting to 116 people. The sampling technique that the researcher uses is the saturated sampling technique, where the data being tested is sourced from the entire population of employees with a total of 116 respondents. Data were collected and tested using SPSS version 26. The results showing this the variables of job promotion, incentives and work motivation simultaneously had a significant effect on employee performance at PT Alco Dana Mandiri.